2015
DOI: 10.1186/s12884-015-0649-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients with eclampsia and severe pre-eclampsia in a rural hospital in Western Tanzania: a retrospective medical record study

Abstract: BackgroundEclampsia and pre-eclampsia are well-recognized causes of maternal and neonatal mortality in low income countries, but are never studied in a district hospital. In order to get reliable data to facilitate the hospital’s obstetric audit a retrospective medical record study was performed in Ndala Hospital, Tanzania.MethodsAll patients diagnosed with severe pre-eclampsia or eclampsia between July 2011 and December 2012 were included. Medical records were searched immediately following discharge or death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
(28 reference statements)
4
27
1
Order By: Relevance
“…In three studies, usage of magnesium sulfate in preeclamptic women to prevent seizures ranged from 74.1 to 100% [12,14,17] similar to our finding of (91.7%). In addition to this, this study revealed that anti-convulsant medication was continued for 24 h postpartum for 177 (73.4%) patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In three studies, usage of magnesium sulfate in preeclamptic women to prevent seizures ranged from 74.1 to 100% [12,14,17] similar to our finding of (91.7%). In addition to this, this study revealed that anti-convulsant medication was continued for 24 h postpartum for 177 (73.4%) patients.…”
Section: Discussionsupporting
confidence: 88%
“…Rates of labor induction vary a great deal across studies. Similar to a rural hospital in Western Tanzania, in this study labor was induced in 38.1% of the patients [17]. In contrast, 47.9% of patients were induced at the Mettu Karl Referral Hospital [12] and 23.4% in governmental hospitals of Addis Ababa [14].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this study the proportion of mothers delivered with cesarean section is 47.8%. This is in-line with the study conducted in Aminu Kano Teaching Hospital, Kano, Nigeria(19) which showed 55.8% patients were delivered by cesarean section, in a rural hospital in Western Tanzania (20) 19% women delivered by Caesarean section, in Amhara Regionreferral hospitals, North West Ethiopia(10) showed 27.9% delivered by cesarean section. This might be due to the fact that eclamptic disorder causes seizure/convulsion which highly associated with fetal distress related placental-insu ciency and causes feto-maternal complications.…”
Section: Discussionsupporting
confidence: 86%
“…A high coverage of those interventions alone does not avoid the occurrence of SMO as shown in our study. Different studies have highlighted that high coverage of essential interventions is not sufficient to reduce maternal morbidity and mortality; they suggest that universal coverage of life-saving interventions needs to be matched with comprehensive emergency care and overall improvements in the quality of maternal health care [ 19 , 27 , 28 ]. Case fatality for hypertensive disorders in pregnancy and/or labour was also high in other studies, illustrating that better treatment of hypertension and starting induction of labour as soon as possible is needed to improve health outcomes [ 15 , 21 , 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%